2006
DOI: 10.2325/jbcs.13.152
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors related to periods to ipsilateral breast tumor recurrence after breast-conserving surgery and measures for preventing recurrence in early breast cancer

Abstract: Although tumor proliferative activity, ER status and ly caused differences in timing of recurrence, standard adjuvant therapy, particularly chemotherapy for early recurrence, was effective in inhibiting recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The feasibility of E-BCS was evaluated in terms of the resection margin status, length of the operation time, blood loss, and postoperative complications. The resection margin status is a risk factor for local recurrence in patients with early breast cancer (15), and it may be a crucial factor for accessing the feasibility of E-BCS. According to previous reports, the resection margin positive rate for E-BCS was 0%-5% (11,12).…”
Section: Discussionmentioning
confidence: 88%
“…The feasibility of E-BCS was evaluated in terms of the resection margin status, length of the operation time, blood loss, and postoperative complications. The resection margin status is a risk factor for local recurrence in patients with early breast cancer (15), and it may be a crucial factor for accessing the feasibility of E-BCS. According to previous reports, the resection margin positive rate for E-BCS was 0%-5% (11,12).…”
Section: Discussionmentioning
confidence: 88%
“…Resection margin status is a risk factor for local recurrence in patients with early breast cancer [14,15], and it may be a crucial factor for accessing EABCS feasibility. The resection margin positive rate for EABCS is 0-5% [5,6,10], compared with about a 10% margin positive rate for conventional BCS [1,16].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological risk factors for IBTR after BCS include close or positive surgical margins [1,3,12,16], presence of extensive intraductal component (EIC) in and/or around the tumor [1,[17][18], presence of lymphovascular invasion (LVI) with or without positive axillary lymph nodes [1,3,7,16,19], histological multifocality [7,16], high histopathological grade [16], negative hormonal receptor status [7], and c-erbB2 oncogene overexpression [20]. Clinical risk factors for IBTR include tumor size [16][17], young age [2][3][18][19], and gross multicentricity [9]; however, a strong family history of breast cancer has been associated with late IBTR and whether these are true recurrences or actually new tumors is controversial [21].…”
Section: Abstract • Background : Inflammatory Local Recurrencementioning
confidence: 99%
“…Some studies report an outcome similar to that reported for inflammatory breast cancer [23][24]; others describe "occult inflammatory breast cancer" as a more benign process. This type of recurrence has been associated with multicentricity [7,[10][11], multifocality [25][26], positive resection margins [7,16], high number of positive lymph nodes [7,25], and LVI [4,[7][8][12][13][14][15].…”
Section: Abstract • Background : Inflammatory Local Recurrencementioning
confidence: 99%
See 1 more Smart Citation